Ethnomycological Knowledge and Nutritional Analysis of Some Wild Edible Mushrooms of Sagarmatha National Park (SNP), Nepal - Giri, Anjana; Rana, Rabina (Journal of Natural History Museum, 2009)
This paper describes the traditional mycological knowledge of Sherpa community of Sagarmatha National Park (SNP) and its adjoining areas (2600-4000 masl). Twenty nine species were identified having ethnomycological use. Among which 26 were identified as edible, 2 as medicine and 1 for decorative purposes. The local communities are well familiar about the morphological feature, habitat and qualities of these mushrooms. The local names of mushrooms have been derived on the basis of their morphological features, nature of growth and colour. The indexes of similarity of edible mushrooms along different forest range from 40-80%. Proximate composition (moisture, ash carbohydrate, crude fat, crude protein and crude fibre) and mineral composition (calcium, phosphorous and iron) of 11 most prized edible mushrooms was investigated. The overall nutritional values of wild edible mushrooms analyzed were good and comparable to other cultivated varieties of mushrooms. Key words: Ethnomycology; edible; mushrooms; nutrition; protein Journal of Natural History Museum Vol. 23, 2008 Page 65-77